Efektivitas dan Risiko Media Digital dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Novel, Novel; Khasairi, Moh. (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to determine the effectiveness of digital innovations in grade VI at MI Al-Mubarokah Pondok Indah Jakarta in Arabic language learning and identify the negative impacts of digital media on student learning behavior. This research method used a case study. The data sources were 20 students and one Arabic teacher, using semi-structured interviews. Data collection techniques use observation, interviews, and documentation. Meanwhile, data analysis involves data reduction, data presentation, and conclusion drawing. The results of this study indicate that digital media-based teaching increases students’ interest in learning, but excessive use decreases students’ intelligence, concentration, and grades. Therefore, a balance is needed between technology-based teaching innovations, character values ​​, and student learning discipline under teacher supervision.